Analisis Kinerja Keuangan Dan Risiko Financial Distress PT Kimia Farma TBK Periode 2020–2024 - Retno Wulandari Putri; Fika Febiati; Sri Retnaning Sampurnaningsih (Journal of Innovative and Creativity, 2026)
This study aims to analyze the financial performance of PT Kimia Farma Tbk during the period 2020–2024 using a financial statement analysis approach. The research employs a qualitative descriptive method utilizing secondary data in the form of the company’s officially published annual financial statements for the period 2020–2024. The analytical techniques applied include horizontal analysis, vertical analysis, financial ratio analysis, and the assessment of financial distress risk using the Altman Z-Score method. The results of the horizontal analysis indicate a significant decline in the financial performance of PT Kimia Farma Tbk starting in 2022, as reflected by weakening liquidity, increasing operating expenses, and a shift from profit to loss during the 2023–2024 period. Meanwhile, the vertical analysis reveals less optimal changes in the financial structure, characterized by an increasing proportion of liabilities to total assets and a declining contribution of profit to sales. The financial ratio analysis shows that PT Kimia Farma Tbk is experiencing financial pressure, as evidenced by low liquidity, a more risky capital structure, and a substantial decline in profitability. These conditions suggest the need for improvements in operational performance and a restructuring of the financial structure to enhance the company’s financial health. Based on the Altman Z-Score analysis, the financial condition of PT Kimia Farma Tbk was classified as being under financial distress in 2020, further deteriorated during the 2021–2022 period, and entered a high financial risk category in 2023–2024. These findings indicate that the company needs to improve cost efficiency, strengthen operational performance, and implement sustainable financial restructuring in order to restore financial health and ensure business continuity in the future.